Crime count and crime harm in a post-socialist city: How does the law of crime concentration at places apply? - Šimon, Martin (European journal of criminology, 2022)
This article reports on a new empirical study evaluating crime concentration at places in a post-socialist city. We use principles of the law of crime concentration at places and the Cambridge Crime Harm Index to measure crime count and crime harm concentration at the level of street segments. The research found differences between crime concentration in a post-socialist city and crime concentration reported by recent studies from US or UK cities. Both crime and harm concentration are consistently less spatially clustered than expected by the theory in a post-socialist city. This finding has significance for both international criminology and national policing authorities, because the success of place-based policing is highly dependent on strong spatial clustering of crime. The study underlines the importance of experimental criminology and theory testing for the transfer of crime prevention approaches from their original contexts.